Polyurethane acrylate polymer encapsulated cadmium-based core-shell quantum dot photoluminescent material and preparation method and application thereof

By using polyurethane acrylate polymer to encapsulate cadmium-based core-shell quantum dots and construct cross-linked structures, the problem of poor quantum dots is solved, and high-stability and high-performance photoluminescent materials are achieved.

CN119410369APending Publication Date: 2025-02-11HANGZHOU INST FOR ADVANCED STUDY UCAS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411537490.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The stability of quantum dots limits their application in complex environments, especially poor stability to light, oxygen, humidity and temperature, which may lead to structural decomposition or phase change and fluorescence quenching.

Method used

The CdSe/CdS quantum dots are encapsulated using polyurethane acrylate polymer, and the crosslinking structure is constructed to improve the environmental stability of the material by introducing crosslinking agents, controlling the initiator dosage and optimizing the preparation process.

Benefits of technology

It effectively improves the environmental stability of quantum dot polymer materials, maintains its optical properties and compatibility with polymers, and meets the needs of high-performance photoluminescent materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410369A_ABST
    Figure CN119410369A_ABST
Patent Text Reader

Abstract

The invention relates to a photoluminescent material of polyurethane acrylate polymer encapsulated cadmium-based core-shell quantum dots and a preparation method and application thereof.The preparation method comprises the steps that after CdSe / CdS quantum dots in a hexane solvent are separated and purified, the CdSe / CdS quantum dots are evenly dispersed in a selected monomer solvent again; the preparation method comprises the following steps: packaging CdSe / CdS quantum dots by using a polyurethane acrylate prepolymer through a direct blending method, uniformly coating a substrate with a packaged quantum dot-polymer mixture through a scraper method, and carrying out UV curing to obtain the quantum dot-polymer nano composite material with high photoluminescence quantum yield. The method has the excellent characteristics of being simple and convenient to operate, high in repeatability, adjustable in macroscopic size and the like. The CdSe / CdS / PUA nano composite material shows good chemical compatibility, meanwhile, the polyurethane acrylate polymer encapsulation layer provides physical isolation for the quantum dots, the reabsorption phenomenon among the quantum dots is effectively reduced, so that the fluorescent property and the luminous efficiency of the quantum dots are kept, and the CdSe / CdS / PUA nano composite material has wide application prospects in the field of photoluminescent materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of quantum dot polymer photoluminescent materials, and in particular to a polyurethane acrylate polymer encapsulated cadmium-based core-shell quantum dot photoluminescent material, and a preparation method and application thereof. Background Art

[0002] Due to their unique optical properties, photoluminescent materials can convert absorbed light energy into light radiation of different wavelengths after being excited by light. They are widely used in display technology, biological imaging, optoelectronic devices and other fields, and have attracted much attention in scientific research and industrial applications.

[0003] Semiconductor quantum dots have the characteristics of high photoluminescence quantum yield, narrow emission line width and highly adjustable emission wavelength. Their excellent photoluminescence properties show great application potential in many fields. However, the stability of quantum dots has always been a key factor limiting their application. For example, they have poor stability to light, oxygen, humidity and temperature, and may undergo structural decomposition or phase change and fluorescence quenching. In practical applications, photoluminescent materials may need to maintain their performance in complex environments, such as high temperature, humidity, ultraviolet irradiation, etc. Therefore, it is crucial to develop photoluminescent quantum dot polymer materials with high stability to ensure their reliability and durability in a variety of application scenarios.

[0004] In view of the above problems, it is urgent to explore how to improve the environmental stability of materials while ensuring the optical properties of quantum dots and their compatibility with polymers, so as to meet the growing demand for high-performance photoluminescent materials. Summary of the invention

[0005] The purpose of the present invention is to provide a photoluminescent material of cadmium-based core-shell quantum dots encapsulated by polyurethane acrylate polymers and a preparation method and application thereof in order to solve the above problems, and to encapsulate CdSe / CdS quantum dots using polyurethane acrylate polymers with good processing performance. By introducing a cross-linking agent to construct a cross-linking structure, controlling the amount of initiator, optimizing the preparation process, ensuring the optical properties of quantum dots and compatibility with polymers, and improving the environmental stability of the material, the growing demand for high-performance photoluminescent materials can be met.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] The first object of the present invention is to provide a method for preparing a photoluminescent material of cadmium-based core-shell quantum dots encapsulated by a polyurethane acrylate polymer, the preparation method comprising the following steps:

[0008] (1) Purification of CdSe / CdS quantum dots: Methyl acetate was added to the CdSe / CdS quantum dot solution to induce phase separation, and the solution was centrifuged to obtain a CdSe / CdS quantum dot precipitate;

[0009] (2) Preparation of CdSe / CdS / IBOA solution: The CdSe / CdS quantum dot precipitate obtained by centrifugal purification in step (1) is redispersed in an isobornyl acrylate monomer solvent, and ultrasonically vibrated until the CdSe / CdS quantum dot precipitate is completely dissolved to obtain a CdSe / CdS / IBOA solution;

[0010] (3) Encapsulation of CdSe / CdS quantum dots by polyurethane acrylate (PUA) polymer: adding a polyurethane acrylate prepolymer and a photoinitiator to the CdSe / CdS / IBOA solution obtained in step (2), mixing and stirring to form a stable orange-red mixture, and then defoaming the mixture under a vacuum environment to obtain a quantum dot polymer mixture;

[0011] (4) Preparation of quantum dot-polymer photoluminescent material: The quantum dot-polymer mixture obtained in step (3) is slowly poured onto a pre-cleaned glass substrate, and after a one-step scraping, it is cured by ultraviolet light; finally, the sample is demolded and cut to obtain a CdSe / CdS / PUA photoluminescent material, that is, the photoluminescent material of the cadmium-based core-shell quantum dots encapsulated by the polyurethane acrylate polymer.

[0012] Furthermore, in step (1), the volume ratio of CdSe / CdS quantum dot solution:methyl acetate is 1:2.

[0013] Furthermore, the CdSe / CdS quantum dot solution is a solution formed by dispersing CdSe / CdS quantum dots in a hexane solvent, and the mass concentration of CdSe / CdS quantum dots in the CdSe / CdS quantum dot solution is 15.00 g / L.

[0014] Furthermore, the centrifugal conditions in step (1) include: centrifuging in a centrifuge, setting the speed of the centrifuge to 8000 rpm and the time to 5 min.

[0015] Furthermore, the time for ultrasonic oscillation in step (2) until the CdSe / CdS quantum dot precipitate is completely dissolved is 0-15 minutes.

[0016] More preferably, the ultrasonic oscillation in step (2) lasts for 10-15 minutes until the CdSe / CdS quantum dot precipitate is completely dissolved, and more preferably, it lasts for 10 minutes.

[0017] Furthermore, in step (2) and step (3), the mass ratio of the polyurethane acrylate prepolymer, the isobornyl acrylate monomer and the photoinitiator is (60-75):(21-36):(2-4).

[0018] Further preferably, in step (2) and step (3), the mass ratio of the polyurethane acrylate prepolymer, the isobornyl acrylate monomer and the photoinitiator is 71:27:2.

[0019] Furthermore, the photoinitiator is a combination of one or more of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) or dimethylbenzil ether (DMPA).

[0020] More preferably, the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO).

[0021] Furthermore, in step (3), the defoaming treatment is carried out by placing the product in a vacuum drying oven and performing the defoaming treatment in a vacuum environment of less than 0.01 Pa.

[0022] Furthermore, in step (4), a scraper coater is used for one-step scraping, and the scraper coater is set to a scraping thickness of 1-2 mm;

[0023] Furthermore, in step (4), the film is placed under an ultraviolet lamp with a central wavelength of 365 nm for ultraviolet light curing, and the curing time is 30-40 minutes.

[0024] Furthermore, in step (4), the doping amount of CdSe / CdS quantum dots in the obtained CdSe / CdS / PUA photoluminescent material is 0.5-5 wt%.

[0025] Furthermore, the preparation method specifically comprises the following steps:

[0026] (1) Purification of CdSe / CdS quantum dots: First, an appropriate amount of methyl acetate was added to a certain amount of CdSe / CdS quantum dot solution dispersed in hexane solvent to induce phase separation, and the speed of the centrifuge was set to 8000 rpm and the time was set to 5 min. The upper clear liquid after centrifugation was removed and the orange-yellow precipitate obtained was CdSe / CdS quantum dots.

[0027] (2) Preparation of CdSe / CdS / IBOA solution: The CdSe / CdS quantum dot precipitate obtained by centrifugal purification was re-stirred and dispersed in an appropriate amount of isobornyl acrylate (IBOA) monomer solvent, and ultrasonically vibrated until the precipitate was completely dissolved to obtain a clear CdSe / CdS / IBOA solution.

[0028] (3) Encapsulation of CdSe / CdS quantum dots by polyurethane acrylate polymer: A certain ratio of polyurethane acrylate (PUA) prepolymer and photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) were added to the CdSe / CdS / IBOA solution, and a stable orange-red mixture was formed by mixing and stirring; the mixture was then placed in a vacuum drying oven and defoamed in a vacuum environment of less than 0.01 Pa.

[0029] (4) Preparation of quantum dot polymer photoluminescent material: The defoamed quantum dot polymer mixture is slowly poured onto a pre-cleaned glass substrate, and is coated in one step using a scraper coater according to a predetermined thickness, and then placed under a UV lamp with a central wavelength of 365 nm for uniform illumination until it is completely cured; finally, the sample is demolded and cut to obtain a CdSe / CdS quantum dot polymer photoluminescent material of corresponding size and shape, that is, the photoluminescent material of the cadmium-based core-shell quantum dots encapsulated by the polyurethane acrylate polymer.

[0030] The second object of the present invention is to provide a photoluminescent material of cadmium-based core-shell quantum dots encapsulated by a polyurethane acrylate polymer, which is prepared by the above-mentioned preparation method. The size and thickness of the photoluminescent material of cadmium-based core-shell quantum dots encapsulated by the polyurethane acrylate polymer are adjustable in the range of 5mm-15mm.

[0031] Furthermore, the polyurethane acrylate polymer encapsulated cadmium-based core-shell quantum dot photoluminescent material has color uniformity, surface continuity and luminescence consistency.

[0032] Furthermore, the photoluminescent material of cadmium-based core-shell quantum dots encapsulated by polyurethane acrylate polymer (i.e., CdSe / CdS / PUA nanocomposite material, or called CdSe / CdS quantum dot polymer photoluminescent material, CdSe / CdS / PUA composite material) exhibits good chemical compatibility. At the same time, the polyurethane acrylate polymer encapsulation layer provides physical isolation for the quantum dots, effectively reducing the reabsorption phenomenon between quantum dots, thereby maintaining their fluorescent properties and luminescence efficiency, and has broad application prospects in the field of photoluminescent materials.

[0033] The third object of the present invention is to provide an application of a photoluminescent material of cadmium-based core-shell quantum dots encapsulated by a polyurethane acrylate polymer prepared by the above-mentioned preparation method, and to apply the photoluminescent material of cadmium-based core-shell quantum dots encapsulated by a polyurethane acrylate polymer to display technology, bioimaging, optoelectronic devices and other fields.

[0034] Compared with the prior art, the beneficial effects of the present invention are embodied in the following aspects:

[0035] 1) The polyurethane acrylate polymer encapsulated cadmium-based core-shell quantum dot photoluminescent material and its preparation method provided by the present invention, when preparing the quantum dot polymer material, the reasonable selection and use of the photoinitiator can reduce the attack of free radicals on CdSe / CdS quantum dots during the photopolymerization process, thereby avoiding the fluorescence quenching phenomenon and maintaining the photoluminescent properties of the quantum dots; the dosage ratio of the IBOA monomer and the PUA prepolymer can ensure that the quantum dots are evenly dispersed in the polymer matrix while avoiding excessive phase separation or aggregation; the purification step can remove surface defects and non-luminescent impurities, and effective purification can reduce the trap state on the surface of the quantum dots, thereby improving the photoluminescent efficiency and color purity of the material. The type and dosage of the photoinitiator, the ratio of the IBOA monomer and the PUA prepolymer, and the doping amount of the quantum dots and other parameters should be tuned within a certain range to optimize the performance of the quantum dot polymer photocuring system.

[0036] 2) The polyurethane acrylate polymer encapsulated cadmium-based core-shell quantum dot photoluminescent material provided by the present invention, the finally prepared CdSe / CdS / PUA composite material has color uniformity, surface continuity and luminescence consistency, and the size thickness is adjustable in the range of 5mm-15mm.

[0037] 3) The polyurethane acrylate polymer encapsulated cadmium-based core-shell quantum dot photoluminescent material provided by the present invention, and its preparation method and application, the present invention obtains a quantum dot-polymer composite material with high doping amount and adjustable size through direct blending method and blade coating technology, and the preparation process is simple, low cost and good repeatability. The prepared composite material is formed by uniformly dispersing core-shell structure quantum dots in a polymer matrix, and has good compatibility and spectral consistency, high fluorescence efficiency and environmental stability even at high doping amounts. It can also be used as an efficient photoluminescent material and applied in optoelectronic systems to achieve effective conversion of light energy and high-quality signal processing.

[0038] 4) The preparation method of the photoluminescent material of cadmium-based core-shell quantum dots encapsulated by polyurethane acrylate polymer provided by the present invention is a method for preparing high-stability photoluminescent materials by encapsulating CdSe / CdS core-shell quantum dots by polyurethane acrylate polymer. The preparation process has the characteristics of operational safety and high repeatability. At the same time, it combines the large Stokes shift characteristics of core-shell quantum dots to reduce self-absorption, which is of great significance for avoiding aggregation-induced fluorescence quenching of quantum dots under high doping amounts and achieving high-efficiency photoluminescence of quantum dots under extreme environments. The preparation method significantly improves the preparation quality of the material with its simplicity, high efficiency and excellent repeatability. Compared with pure quantum dot materials, it not only retains the high fluorescence efficiency characteristics of core-shell quantum dots, but also effectively restricts the movement of quantum dots by introducing a polymer cross-linking network, reduces non-radiative recombination caused by changes in external factors such as temperature, and is more conducive to the development and application of photoluminescent materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 These are pictures of the CdSe / CdS / PUA composite material with a quantum dot doping amount of 1 wt% obtained in Example 1 of the present invention under indoor lighting and ultraviolet light (365 nm), wherein a and c are front views under indoor lighting, b is a side view under indoor lighting, and d is a front view under ultraviolet light (365 nm).

[0040] Figure 2 The CdSe / CdS / PUA composite material samples with different quantum dot doping amounts of the present invention are shown in Figure 1. From left to right, and from top to bottom, the quantum dot doping amounts are 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt% and 5wt% respectively.

[0041] Figure 3 The fluorescence emission and absorption spectra of the CdSe / CdS / PUA composite material with different quantum dot doping amounts (1wt%, 2wt%, 3wt%, 4wt% and 5wt%) of the present invention.

[0042] Figure 4 The PLQY diagrams of the stability of CdSe / CdS / PUA composite materials with different quantum dot doping amounts (1wt%, 2wt%, 3wt%) of the present invention are shown in Figure a. The high humidity storage stability study is placed in water, b. The light stability study is under 30W ultraviolet light (365nm), and c. The high temperature storage stability study is at 60°C. DETAILED DESCRIPTION

[0043] The present invention is described in detail below in conjunction with specific embodiments, but is by no means intended to limit the present invention. Features such as preparation methods, materials, structures or composition ratios not explicitly described in this technical solution are considered to be common technical features disclosed in the prior art.

[0044] The following examples will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several modifications and improvements may be made without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.

[0045] The practice of the present invention may employ conventional techniques of chemistry within the skill of the art. In the following examples, efforts have been made to ensure accuracy with respect to the numbers used (including amounts, temperatures, reaction times, etc.), but some experimental errors and deviations should be taken into account.

[0046] CdSe / CdS quantum dots were homemade, and the wurtzite-type CdSe core was synthesized and the CdS shell was grown according to the preparation method of the reference “Compact high-quality CdSe–CdS core–shell nanocrystals with narrow emission linewidths and suppressed blinking”.

[0047] Polyurethane acrylate (PUA) is a hydrophobic bifunctional polyurethane acrylate purchased commercially from Nanjing Runao New Material Technology Co., Ltd.

[0048] 2,4,6-Trimethylbenzoyl-diphenylphosphine oxide (TPO) and dimethylbenzil ether (DMPA) were both commercially available.

[0049] Example 1

[0050] This embodiment provides a method for preparing a photoluminescent material of cadmium-based core-shell quantum dots encapsulated by polyurethane acrylate polymer, comprising the following steps:

[0051] (1) Weigh the mass m of the empty centrifuge tube 1 g; add CdSe / CdS quantum dot solution dispersed in hexane solvent (the mass concentration of CdSe / CdS quantum dots in the CdSe / CdS quantum dot solution is 15.00 g / L) and methyl acetate solvent (the volume ratio of CdSe / CdS quantum dot solution to methyl acetate is 1:2) into a blank centrifuge tube; set the centrifuge speed to 8000 rpm and the time to 5 min; remove the supernatant after centrifugation, and collect the orange-yellow precipitate, which is CdSe / CdS quantum dots; weigh the total mass m of CdSe / CdS quantum dots and centrifuge tube 2 g, and the CdSe / CdS quantum dot mass m is obtained 0 (m 0 =m 2 -m 1 )g.

[0052] (2) Weigh 27m 0 g isobornyl acrylate (IBOA) was used as a monomer solvent, and the CdSe / CdS quantum dot precipitate obtained by centrifugal purification was dispersed therein, stirred for 5 minutes, and then placed in a high-frequency ultrasonic machine with a frequency of 40 kHz for ultrasonic oscillation treatment for 10 minutes until the precipitate was completely dissolved to form a clear orange-red CdSe / CdS / IBOA solution.

[0053] (3) Weigh 2m 0 g 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) photoinitiator was added to the CdSe / CdS / IBOA solution and stirred for 10 min to ensure its complete dissolution; 71 m 0 g polyurethane acrylate (PUA) prepolymer is added to the mixed system and continuously stirred at room temperature until a uniform orange-red viscous mixture is formed; the quantum dot polymer mixture is placed in a vacuum drying oven and defoamed for 30 minutes in a vacuum environment of less than 0.01 Pa at room temperature to remove bubbles in the mixture and ensure the homogeneity of the material, thereby obtaining a defoamed quantum dot polymer mixture.

[0054] (4) Clean and wash the transparent glass substrate with ethanol and dry it in an oven at 50°C; slowly pour the defoamed quantum dot polymer mixture onto the glass substrate to avoid generating excess bubbles; adjust the thickness of the scraper coater to 1 mm and scrape the mixture on the substrate in one step; place it under a UV lamp with a central wavelength of 365 nm and evenly illuminate it for 40 minutes until the material is completely cured, then demold it and cut it into CdSe / CdS / PUA photoluminescent materials with a size of 10 mm×10 mm×1 mm.

[0055] In this embodiment, the quantum dot doping mass concentration is m 0 / (27m 0 +2m 0 +71m 0 )=1wt%. The macroscopic morphology of the CdSe / CdS / PUA photoluminescent material obtained in this example was observed under indoor lighting and ultraviolet light (365nm). For details, please refer to Figure 1 .

[0056] Example 2

[0057] This example mainly examines the effects of raw material ratio, quantum dot doping amount, high-frequency ultrasonic oscillation, photoinitiator type and amount on the preparation of high-stability photoluminescent materials during the polyurethane acrylate polymer encapsulation of CdSe / CdS core-shell quantum dots. Figure 2As shown, the sample images of the CdSe / CdS / PUA photoluminescent material obtained in this embodiment under the conditions of quantum dot doping amounts of 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt% and 5wt% (serial numbers 12 to 17) are shown. By observing the macroscopic morphology, the CdSe / CdS / PUA photoluminescent material has color uniformity and surface continuity; Figure 3 The fluorescence emission and absorption spectra of CdSe / CdS / PUA photoluminescent materials with different quantum dot doping amounts (1wt%, 2wt%, 3wt%, 4wt% and 5wt%, serial numbers 13 to 17) show that the CdSe / CdS / PUA photoluminescent materials have luminescence consistency, and the PL emission peaks are all around 655nm, without obvious red shift. Please refer to Example 1 for the specific experimental steps, except that: the raw material ratio (mass ratio of PUA and IBOA), quantum dot doping amount (the mass of CdSe / CdS quantum dots in the obtained CdSe / CdS / PUA photoluminescent material is the percentage of the total mass of prepolymer, monomer and photoinitiator), high-frequency ultrasonic oscillation, photoinitiator type and amount (the amount of photoinitiator refers to the mass fraction of the photoinitiator as a percentage of the total mass of prepolymer, monomer and photoinitiator) are changed respectively. The specific experimental parameters are shown in Table 1.

[0058] Table 1 Experimental conditions for preparing the above CdSe / CdS / PUA photoluminescent materials:

[0059]

[0060]

[0061] As shown in the table, the raw material ratio of PUA and IBOA will affect the viscosity of the polymer before curing. The viscosity of the PUA prepolymer used is 9575mPa·s@60℃. Too high polymer viscosity is not conducive to the effective dispersion of quantum dots in the polymer matrix. Therefore, it is necessary to add low molecular weight monomers as active diluents to reduce the viscosity of the prepolymer. By adjusting the mass ratio of prepolymer to monomer, a suitable polymer viscosity is obtained to prevent quantum dots from agglomerating and limit the interaction between quantum dots and free radicals. According to experiments, it is more appropriate to select a mass ratio of PUA and IBOA of 71:27; high-frequency ultrasonic oscillation has a certain effect on the dispersion of purified quantum dots in the monomer solution. The high-frequency vibration generated by ultrasound can generate strong shock waves, overcome the soft agglomeration of quantum dots due to van der Waals forces and electrostatic forces, and improve the dispersibility of quantum dots in the monomer solution; at the same time, the type and amount of photoinitiator will also affect the photoluminescence quantum yield of quantum dot-polymer nanocomposites. The free radicals generated by the photoinitiator during UV curing may cause the degradation of the optical properties of quantum dots during the polymerization reaction. The photolysis products of TPO are trimethylbenzoyl radicals and diphenylphosphine radicals, and the photolysis products of DMPA are benzoyl radicals and dimethoxybenzyl radicals. The latter's benzyl structure can also continue to crack to generate methyl radicals and methyl benzoate. Free radicals can interact with the surface of quantum dots, leading to ligand desorption and oxidation of the quantum dot shell, thereby producing defects that lead to non-radiative transitions and reduce the luminescence efficiency of quantum dots. Therefore, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) is selected as the photoinitiator, and the mass fraction of the photoinitiator is 2wt% to avoid excessive increase of free radicals and affect the optical properties of the material; by changing the quantum dot doping amount (0.5-5wt%), within this range, the increase in the quantum dot doping amount has no significant effect on the fluorescence emission (PL) characteristics of the prepared nanocomposite material, and the PLQY results can be maintained above 90%.

[0062] Example 3

[0063] This example investigates whether the highly doped CdSe / CdS / PUA sample obtained in Example 1 can be used as a photoluminescent material to ensure high optical properties under extreme conditions.

[0064] The experimental equipment in this example is the QE Pro spectrometer integrating sphere system. The specific experimental steps are: First, turn on the 365nm laser, irradiate the excitation light onto the integrating sphere sample stage, obtain the excitation spectrum, and obtain the total number of photons. Then, place the cut CdSe / CdS / PUA samples (samples with different quantum dot doping amounts (1wt%, 2wt%, 3wt%) obtained in Example 2, i.e., serial numbers 13, 14, and 15) in the solid groove of the integrating sphere sample stage, turn on the excitation light source so that the sample is excited by light to produce photoluminescence; the integrating sphere system collects all photoluminescence signals emitted from the sample, including the number of unabsorbed photons and the number of emitted photons. Use the integrating sphere system supporting software to calculate the ratio of the number of emitted photons to the number of absorbed photons to obtain the absolute quantum yield of the sample. We placed CdSe / CdS / PUA samples with different quantum dot doping amounts in an environment without inert gas protection, immersed them directly in water, irradiated them directly with ultraviolet light (30W), and placed them in a drying oven at 60°C for a period of time. We then remeasured the PLQY of the samples and compared the results with those of the original samples. The experimental results are shown in Figure 2. Figure 4 As shown, Figure 4 The high temperature and high humidity and light stability test diagram of the CdSe / CdS / PUA photoluminescent material shows that when the sample is directly immersed in water and directly irradiated with ultraviolet light (30W) for a period of time, the PLQY of the CdSe / CdS / PUA sample has an insignificant downward trend within 200 hours. Compared with the original sample, the relative PLQY value can basically be maintained above 0.8. When the sample is placed in a drying oven at 60°C for a period of time, the PLQY of the CdSe / CdS / PUA sample has an insignificant downward trend within 200 hours. Compared with the original sample, the relative PLQY value can basically be maintained above 0.6. Under the tested environmental conditions, the PLQY of the CdSe / CdS / PUA sample has an insignificant downward trend. The quantum dot-polymer nanocomposite material of the present invention has a better environmental stability to ensure excellent optical properties.

[0065] The above is a description of the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above-mentioned description of the embodiments for the convenience of ordinary technicians in the technical field to understand and use the invention. It is obvious that those familiar with the technology in the field can easily make various modifications to these embodiments and apply the general principles described here to other embodiments without creative work. Therefore, the present invention is not limited to the above-mentioned embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A method for preparing a photoluminescent material of polyurethane acrylate polymer encapsulated cadmium-based core-shell quantum dots, characterized in that: The preparation method comprises the following steps: (1) Purification of CdSe / CdS quantum dots: Methyl acetate is added to the CdSe / CdS quantum dot solution, and the solution is centrifuged to obtain a CdSe / CdS quantum dot precipitate; (2) Preparation of CdSe / CdS / IBOA solution: The CdSe / CdS quantum dot precipitate obtained by centrifugal purification in step (1) is redispersed in an isobornyl acrylate monomer solvent, and ultrasonically vibrated until the CdSe / CdS quantum dot precipitate is completely dissolved to obtain a CdSe / CdS / IBOA solution; (3) Encapsulation of CdSe / CdS quantum dots by polyurethane acrylate polymer: adding polyurethane acrylate prepolymer and photoinitiator to the CdSe / CdS / IBOA solution obtained in step (2), mixing and stirring to form a mixture, and then defoaming the mixture under vacuum to obtain a quantum dot polymer mixture; (4) Preparation of quantum dot-polymer photoluminescent material: pour the quantum dot-polymer mixture obtained in step (3) onto a glass substrate, perform a one-step scraping, and then cure it under ultraviolet light; finally, demold and cut the sample to obtain a CdSe / CdS / PUA photoluminescent material, which is the photoluminescent material of cadmium-based core-shell quantum dots encapsulated by the polyurethane acrylate polymer.

2. The method for preparing a photoluminescent material of polyurethane acrylate polymer encapsulated cadmium-based core-shell quantum dots according to claim 1, characterized in that: In step (1), the volume ratio of CdSe / CdS quantum dot solution:methyl acetate is 1:

2.

3. The method for preparing a photoluminescent material of polyurethane acrylate polymer encapsulated cadmium-based core-shell quantum dots according to claim 1, characterized in that: The centrifugal conditions in step (1) include: centrifuging in a centrifuge, setting the speed of the centrifuge to 8000 rpm and the time to 5 min.

4. The method for preparing a photoluminescent material of polyurethane acrylate polymer encapsulated cadmium-based core-shell quantum dots according to claim 1, characterized in that: The time for ultrasonic oscillation in step (2) until the CdSe / CdS quantum dot precipitate is completely dissolved is 0-15 minutes.

5. The method for preparing a photoluminescent material of polyurethane acrylate polymer encapsulated cadmium-based core-shell quantum dots according to claim 1, characterized in that: The mass ratio of the polyurethane acrylate prepolymer, isobornyl acrylate monomer and photoinitiator in step (2) and step (3) is (60-75):(21-36):(2-4).

6. The method for preparing a photoluminescent material of polyurethane acrylate polymer encapsulated cadmium-based core-shell quantum dots according to claim 1, characterized in that: The photoinitiator is a combination of one or more of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and benzil dimethyl ether.

7. The method for preparing a photoluminescent material of polyurethane acrylate polymer encapsulated cadmium-based core-shell quantum dots according to claim 1, characterized in that: In step (4), a scraper coater is used for one-step scraping, and the scraper coater is set to a scraping thickness of 1-2 mm; in step (4), it is placed under an ultraviolet lamp with a central wavelength of 365 nm for ultraviolet light curing, and the curing time is 30-40 minutes.

8. The method for preparing a photoluminescent material of polyurethane acrylate polymer encapsulated cadmium-based core-shell quantum dots according to claim 1, characterized in that: In step (4), the doping amount of CdSe / CdS quantum dots in the obtained CdSe / CdS / PUA photoluminescent material is 0.5-5 wt %.

9. A photoluminescent material of cadmium-based core-shell quantum dots encapsulated by a polyurethane acrylate polymer prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The photoluminescent material of the polyurethane acrylate polymer encapsulating the cadmium-based core-shell quantum dots has a size and thickness of 5 mm to 15 mm.

10. An application of a photoluminescent material of cadmium-based core-shell quantum dots encapsulated by a polyurethane acrylate polymer prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The photoluminescent material of the polyurethane acrylate polymer encapsulating cadmium-based core-shell quantum dots is applied to the fields of display technology, biological imaging, and optoelectronic devices.